2019
DOI: 10.9734/ajfar/2019/v5i130066
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities of Culture Water and African Catfish Reared in Different Aquaculture Systems in Nigeria Analyzed Using Culture Dependent Techniques

Abstract: The microbial communities of culture water and catfish C. gariepinus from three replicates of earthen, concrete and tarpaulin ponds in Nigeria were analyzed. Waters was collected from 25 cm below pond water surface per culture system. Three catfish per replicate system were also collected and analyzed in the lab. Catfish gut, skin and gills were analyzed. Earthen ponds had significantly more diverse microbial community and coliform forming units (CFU/ml) 2.43 x10-4 CFU/ml than the rest systems. Earthen ponds h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Our study agrees with the findings of Njoku et al [29], who reported the presence of Escherichia coli, Salmonella spp., Staphylococcus aureus, Proteus spp, Klebsiella spp, and Enterobacter in some fish pond water within the Niger Delta region of Nigeria. The result also agrees with Uchechukwu & Okoli [30], The bacteria: Staphylococcus aureus and Escherichia coli in the catfish samples are the commonest bacteria found in the fish samples. Escherichia coli has been identified as a potential cause of diarrhoea and kidney damage as well as uncomplicated community-acquired urinary tract infections [31].…”
Section: Discussionsupporting
confidence: 90%
“…Our study agrees with the findings of Njoku et al [29], who reported the presence of Escherichia coli, Salmonella spp., Staphylococcus aureus, Proteus spp, Klebsiella spp, and Enterobacter in some fish pond water within the Niger Delta region of Nigeria. The result also agrees with Uchechukwu & Okoli [30], The bacteria: Staphylococcus aureus and Escherichia coli in the catfish samples are the commonest bacteria found in the fish samples. Escherichia coli has been identified as a potential cause of diarrhoea and kidney damage as well as uncomplicated community-acquired urinary tract infections [31].…”
Section: Discussionsupporting
confidence: 90%